2001
DOI: 10.1038/sj.ijo.0801705
|View full text |Cite
|
Sign up to set email alerts
|

The false hope syndrome: unrealistic expectations of self-change

Abstract: People appear to behave paradoxically, by persisting in repeated self-change attempts despite previous failures. It is argued, though, that self-change attempts provide some initial rewards even when unsuccessful. Feelings of control and optimism often accompany the early stages of self-modification efforts. In addition, unrealistic expectations concerning the ease, speed, likely degree of change, and presumed benefits of changing may overwhelm the knowledge of one's prior failures. It is thus important to lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 21 publications
2
49
0
3
Order By: Relevance
“…It has been frequently argued that false hope and the desire to lose more weight than what realistically can be expected may Predictors of success in weight loss PJ Teixeira et al increase the likelihood of early disappointment and relapse upon smaller than wanted changes. 49,50 The present and our previous report 11 are the first studies to have shown empirical data to support this claim. Others recently reported that weight goals and dream weights were not associated with weight loss, in a completers-only follow-up analysis of a 8-week treatment program (47% attrition at 18 months).…”
Section: Discussionsupporting
confidence: 74%
“…It has been frequently argued that false hope and the desire to lose more weight than what realistically can be expected may Predictors of success in weight loss PJ Teixeira et al increase the likelihood of early disappointment and relapse upon smaller than wanted changes. 49,50 The present and our previous report 11 are the first studies to have shown empirical data to support this claim. Others recently reported that weight goals and dream weights were not associated with weight loss, in a completers-only follow-up analysis of a 8-week treatment program (47% attrition at 18 months).…”
Section: Discussionsupporting
confidence: 74%
“…This procedure has been validated in other areas such as the induction of anger, 26,27 anxiety, 27,28 disgust, 28 and happiness. 27 Compared with the other induction procedures, guided imagery vignettes have the advantages of ensuring participants are exposed to the same stimuli (e.g., compared with reliance on autobiographical memory in which recollected incidents of body dissatisfaction may vary widely in their intensity across participants), 29 providing participants with an interpretative framework rather than allowing participants to interpret the material for themselves (e.g., as occurs in exposure to media images of thin women where participants may engage in body esteem-enhancing cognitive processes such as the ''false-hope syndrome''), 30 and ease of administration (e.g., compared with procedures involving confederates). 31 Three vignettes designed to induce body dissatisfaction, negative mood, and a neutral mood state, respectively were developed for the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Despite clear evidence that modern lifestyles, increasing professional demands, the focus on technology and the influence of the media facilitate sedentary behavior and unhealthy dietary practices, it is possible that noncompliance with lifestyle modifications occurs partly because the effectiveness of this strategy does not match up to the individual's expectations 15 . Social pressure often demands improbable weight loss, thereby creating a highly favorable environment for unproven practices.…”
Section: Introductionmentioning
confidence: 99%